Effectiveness of infiltrant in white spot lesions in different depths: an integrative review (Research, Society and Development, 2024)
Objective: To analyze the effectiveness of Icon infiltrant in clinical settings for the treatment of white spot lesions, considering its performance at various dental depths. Methodology: Involved the search and selection of studies analyzing the effectiveness of Icon infiltrant in clinical settings. 244 articles were identified, of which 10 were selected for results analysis. Results and Discussion: Treatment preference may depend on specific clinical situations and patient needs. Comparative studies demonstrated the equivalence or superiority of infiltrant resin over other techniques, highlighting its effectiveness in both short and long term. Furthermore, the importance of the adaptability of resin infiltration to different dental conditions and lesion depths can be emphasized. The aesthetic and minimally invasive approach of the technique was highlighted, as well as its ability to provide stable and long-lasting results. Quantitative assessments offered an objective perspective on post-orthodontic treatment aesthetic improvement, while comparative case studies enriched understanding of nuances in choosing appropriate treatment. Conclusion: Integrative review confirms the effectiveness of resin infiltration, positioning it as a versatile, effective, and long-lasting clinical intervention in the treatment of dental lesions, especially white spots and enamel defects. Consideration of aspects such as long-term stability, patient preference, and adaptation to different dental depths reinforces its relevance in the dental field.